Nursing Students’ Perceptions of the Ease of Use and Usefulness of Immersive Virtual Reality Simulation: A Mixed-Methods Study - Hege Vistven Stenseth RN, MNSc; Marit Hegg Reime RN, Cand.Polit.; Hilde Sundfær BEd; Camilla Olaussen RN, PhD (SAGE Open Nursing)
Introduction Nursing education must equip students with skills for systematic patient assessment, using approaches such as the Airway, Breathing, Circulation, Disability, Exposure (ABCDE) assessment and the National Early Warning Score 2 (NEWS2) for early detection of patient deterioration. Immersive virtual reality (IVR) simulations offer a valuable tool for enhancing competency in these two methods. Objective This study explored nursing students’ experiences with and perception of the ease of use and usefulness of IVR simulations to develop knowledge and skills of the ABCDE assessment and NEWS2 score and to inform future instructional and pedagogical design. Methods A concurrent mixed-methods design was employed. The participants were Bachelor of Nursing students engaged in an IVR simulation focused on developing on ABCDE and NEWS2 Qualitative data were obtained through three focus group interviews involving 18 participants. Quantitative data ( N  = 107) were collected via a postintervention survey. Data analyses were conducted concurrently, and juxtaposed to identify commonalities and discrepancies, with particular attention given to complementary findings. Results Four themes were generated through the qualitative analysis: Navigating Virtual Reality; Bridging Theory and Practice; Empowering Autonomy; and Authenticity and Ambiguity. Survey results for ease of use indicated high score for ease of use, with average score 4.38 out of 5 ( SD 0.32). The average usefulness score was 4.40 ( SD 0.67), implying the IVR simulation as beneficial for enhancing competencies on ABCDE assessment and NEWS2 scoring skills. Conclusion Nursing students generally perceived the IVR technology and software as user-friendly and effective in enhancing their knowledge and skills through repetitive practice with a variety of virtual patients. Customizing IVR simulations to align with students’ competency levels is recommended. Future research should investigate the impact of IVR on learners with differing learning styles, experiences, and levels of technological proficiency, and compare its effectiveness to traditional simulations for skill acquisition.